Can Canada learn from the European Health Data Space? - Joseph Donia; Kimberlyn McGrail; Luca Marelli (Canadian Journal of Public Health, 2026)
Abstract Federal, provincial, and territorial governments in Canada are increasingly committed to promoting health data access and use. The European Union has advanced a bold vision for health data integration with the European Health Data Space (EHDS) Regulation, which entered into force in March 2025. As the first data space to take shape as part of the broader European Strategy for Data, the EHDS establishes a robust regulatory regime for both primary use (clinical care, including electronic health record certification) and secondary use (research, policymaking, and innovation). In this commentary, we outline what Canada can learn from the EHDS policy experience to ensure that debates about health data access and use in Canada remain connected to broader discussions about community rights, accountability, public value, and the practical challenges of integrating data across jurisdictions. In particular, we suggest a more explicit focus on the politics of health data access and use; a value-oriented approach; and situating individual rights in relation to community-oriented governance.